Photoacclimation to light-limitation in a clionaid sponge; implications for understanding sponge bioerosion on turbid reefs. (October 2018) - Marlow, Joseph; Davy, Simon K.; Haris, Abdul; Bell, James J.
Abstract: Watershed-based pollution is a common form of coral reef degradation. Affected reefs are often highly turbid, where light-limitation confines the distribution of photosynthetic benthic taxa and the capacity for photoacclimation is important for survival. We investigated low light photoacclimation in a Symbiodinium- hosting bioeroding sponge using in situ PAM fluorometry. Cliona aff. viridis was artificially shaded (70 & 95% ambient light reduction) on a low turbidity Indonesian reef for 25 days, with a subsequent 14-day recovery period. Significant changes in rETRmax, and qP, and a non-significant but observable decline in Ek, demonstrated that C. aff. viridis is able to photoacclimate to conditions of extreme light reduction and recover within a relatively short period of time. The sponge is therefore unlikely to be light limited on even the most turbid reefs. However, other aspects of watershed-pollution such as sedimentation may still limit their distribution in affected coastal waters. Highlights: Photoacclimation of Symbiodinium- containing clionaid sponges investigated. Cliona aff. viridis was capable of photoacclimating to extreme light reduction. Cliona aff. viridis survived and recovered from 25 days of near darkness. Cliona aff. viridis is unlikely to be light-limited on turbid coral reefs.